2021
DOI: 10.1186/s13287-021-02496-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy in pulmonary fibrosis: a meta-analysis of preclinical studies

Abstract: Background Pulmonary fibrosis (PF) is a devastating disease characterized by remodeling of lung architecture and abnormal deposition of fibroblasts in parenchymal tissue and ultimately results in respiratory failure and death. Preclinical studies suggest that mesenchymal stem cell (MSC) administration may be a safe and promising option in treating PF. The objective of our meta-analysis is to assess the efficacy of MSC therapy in preclinical models of PF. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Unlike the residential MSCs, implantations of external MSCs are reported with effective and protective functions in the treatment of fibrotic diseases in both pre-clinical and clinical studies [ 36 , 190 , 201 , 202 ]. These MSCs are in vitro amplified either from autologous (cells derived from the same individual) or allogeneic (cells derived from the same species but not the same individual) sources (Fig.…”
Section: Mscs In Fibrotic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the residential MSCs, implantations of external MSCs are reported with effective and protective functions in the treatment of fibrotic diseases in both pre-clinical and clinical studies [ 36 , 190 , 201 , 202 ]. These MSCs are in vitro amplified either from autologous (cells derived from the same individual) or allogeneic (cells derived from the same species but not the same individual) sources (Fig.…”
Section: Mscs In Fibrotic Diseasesmentioning
confidence: 99%
“…Surprisingly, greater therapeutic potential of MSCs was discovered as more complex functional mechanisms of these cells were revealed over the decades, including its immunomodulatory capabilities [ 18 ], autocrine and paracrine effects [ 19 ], and the abilities to escape from the innate immune system and counteract the complement system [ 20 ]. Therefore, the clinical application of MSCs has been extensively attempted for various diseases, such as osteoarthritis [ 21 ], rheumatoid arthritis [ 22 ], tissue repair [ 23 25 ], diabetic foot ulcer [ 26 ], diabetes [ 27 ], female infertility [ 28 ], autoimmune diseases [ 29 ], cardiovascular diseases [ 30 ], neurodegenerative diseases [ 31 ], graft versus host disease (GvHD) [ 32 ], COVID-19 patients [ 33 ], and different types of fibrotic diseases [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, MSCs showed anti-fibrotic effects on irradiated lungs via endogenous secretion of HGF and PGF2 19 and robust regulatory T-cell induction in bleomycin-induced pulmonary fibrosis 20 . In a metaanalysis of preclinical studies, Li et al (2021) analyzed 24 articles on the treatment of pulmonary fibrosis in an animal model using MSCs; this analysis showed that MSC therapy improved the survival rate and reduced pulmonary fibrosis scores 21 . In a recent review, Chen et al…”
Section: Commentmentioning
confidence: 99%
“…PF is traditionally considered to be an irreversible lung disease that is refractory to various treatments, resulting in high rates of mortality and morbidity [ 9 ]. Recently, the administration of mesenchymal stem cells (MSCs) has emerged as a promising therapy for PF [ 10 , 11 ]. MSCs have been isolated from various tissues such as the bone marrow, adipose tissue, and the stroma of organs.…”
Section: Introductionmentioning
confidence: 99%